Estimating the Impact of School Education on Contraception Use among Adolescents Aged 15–19 in Burkina Faso and Nigeria: Evidence from a Heckman Two-Step Correction Model - Bago, Jean-Louis; Lompo, Miaba, Louise; Souratié, Wamadini dite Minata (My University, 2018)
Sexually Transmitted Infections (STIs) still raise serious concerns for adolescents’ sexual health in west-African developing countries. To this extent, promoting contraception use among sexually active adolescents is a major key to addressing this problem. Yet, the rate of contraception use by adolescents remains surprisingly low in these countries. Using the Demographic Health Survey of Burkina Faso (2014) and Nigeria (2013), this paper examines the influence of school education on contraception use among sexually active male and female adolescents aged 15-19 in Burkina Faso and Nigeria. The standard estimates using Probit regressions suggest that achieving a primary school education increases the probability of a sexually active adolescent to use contraception by 8.26 percentage points (Burkina Faso) and 17.2 percentage points (Nigeria). This effect increases to 20.3 percentage points (Burkina Faso) and 34.7 percentage points (Nigeria) for adolescents with a secondary or higher school education. However, these baseline estimates are biased because adolescents’ decision to engage into sexual activity is not random. In light of this, a Heckman Correction Model (HCM) has been applied to account for this selection bias. The results show that the Probit regressions underestimate the effect of education on adolescents’ likelihood to use contraception in Burkina Faso and overestimate this effect in Nigeria. In fact, compared to adolescents with no school education, HCM estimates show that adolescents with primary and secondary (or higher) school education have respectively 10.2 and 24.4 percentage points more in the use of contraception in Burkina Faso and 15.1 and 34 percentage points in Nigeria. Together, these results suggest that the exposure to school education increases contraception use among the adolescents in both Burkina Faso and Nigeria.
Supplemental Materials: https://osf.io/qk3a9/
Keywords: school education; contraception; adolescent; Heckman Correction Model; sexually transmitted infections